Syndicate Group Method for Newborn Care with the Knowledge of Posyandu Cadres in the Working Area of the Tamalanrea Health Center, Makassar City - Andriani, Fitri; Kamaruddin, Muh. Ihsan; Sari, Lili Purnama (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Learning methods are the methods used by teachers in carrying out their functions as a tool to achieve learning goals. The PAI learning method is more procedural in nature. “There is a method for everything, and the method of entering heaven is knowledge. Newborn babies have a high risk of death. The reason is that knowledge and simple care practices such as preventing hypothermia, giving colostrum and exclusive breastfeeding are still very lacking. Cadres are one of the closest people who can influence changes in the behavior of BBL mothers, so that cadres can provide correct information and influence the knowledge of mothers and families if the cadre's knowledge is good. This research aims to obtain information from the analysis of the influence of newborn care education using the Syndicate Group method on the knowledge of posyandu cadres in the working area of the Tamalarea Community Health Center. The method used in this research was a pre-experiment with a one group pretest-posttest approach with a sample of 24 posyandu cadres in the Tamalarea posyandu working area registered by the village midwife. Before the intervention, 58.3% of posyandu cadres were classified as having sufficient knowledge and 66.7% of posyandu cadres were classified as good knowledge after the intervention. Hypothesis analysis using the Wilcoxon Signed Rank Test with α = 0.05 obtained p value = 0.001, which shows that there is a significant influence of newborn care education using the Syndicate Group method on the knowledge of posyandu cadres. It is hoped that the community health center and village midwives can continue efforts to increase cadre knowledge using interactive methods such as Syndicate Groups and other methods, so that the role of cadres becomes more optimal.